KUALITAS PARTISIPASI POLITIK PEMILIH PEMULA DALAM PEMILU 2024 DI KOTA SERANG - Murfatiah, Siti; Maulana, Delly (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
Indeed, political participation in elections is an important aspect of a democratic system, which includes various activities that aim to influence public policy and the selection of policymakers. Several surveys indicate that new voters are among the largest group of voters in the 2024 elections, including in Serang City. As swing voters who are easily influenced by certain interests, it is necessary to have interesting activities that involve novice voters as well as in-depth education related to election information. This research uses qualitative research with primary data obtained from individuals who have information related to the issues and focus of the research. We obtained secondary data from various sources, including the official website of the General Election Commission, books, reports, journals, and other references. The results indicate that novice voters in Serang City have a fairly good level of participation, with most of them participating as part of the organizers or supervisors of the 2024 elections at each polling station in Serang City. However, there are several problems, namely, misunderstanding between the new rules and the community, the spread of fake news about the 2024 elections, and the Recapitulation Information System (Sirekap) application, which often experiences problems. In addition, there are novice voters who are apathetic towards the electoral process, so efforts need to be made by all stakeholders.